Mind perception and fan fiction: a survey using the IDOLM@STER series - Tetsuya Matsui (Cogent Social Sciences)
This study focuses on the relationship between the impression a character makes on players of a game and the percentage of hetero and homosexualistic fan fiction that uses that character, particularly in the case of femslash works in homosexual fanfiction, which have not been well-studied. An agency/experience model was used as a measure of the impression a character makes on the player. The games analyzed were two games belonging to the same series with different characteristics. One is ‘THE IDOLM@STER Cinderella Girls,’ and the other is ‘THE IDOLM@STER SHINY COLORS’. ‘THE IDOLM@STER Cinderella Girls’ is a game in which the characters do not grow in the storyline and the interaction with the player is not very in-depth. I defined such games as synchronic story games. ‘THE IDOLM@STER SHINY COLORS’ is a game in which the characters grow in the story and reveal much of their inner life through interaction with the player. I defined such games as diachronic story games. Agency and experience were measured for the characters in each of these two games in a questionnaire survey on the web. At the same time, the percentage of hetero and homosexualistic fan fiction in fan fiction for each character posted on the web was investigated. The results showed a significant correlation between character agency and the percentage of homosexualistic fan fiction for the synchronic game, and for the diachronic game, there was a significant correlation between character experience and the percentage of homosexualistic fan fiction.